The Impact Of Diet And Nutrition On Oral Health: A Systematic Review - Tohary, Ismail Ali; Jan, Anas Saifullah; Alotaibi, Majed Abdulhadi; alosaimi, Tariq burayk abdulkareem; Alotaibi, Abdulaziz Eid Ali; alshayb, Abdullah abdulaah; Sadig, Jabeer Abdullah Ahmed; Tumayhi, Hussain Yahya Ahmed; Rubayyi, Seham Hadi; Amri, Sultan Abdullah; Almutairi, Hamed Theyab (Migration Letters, 2022)
The impact of diet and nutrition on oral health is an area of significant interest among researchers and healthcare professionals. This review aimed to assess the current evidence on the relationship between diet, nutrition, and oral health status. The study utilized secondary data from existing research studies, clinical trials, and systematic reviews to establish a comprehensive overview of the topic. The findings of the review highlighted the significant role that diet and nutrition play in maintaining a healthy oral cavity. A diet rich in fruits, vegetables, and lean proteins and low in sugars and processed foods was related to better oral health outcomes, including reduced risk of den[1]tal caries, periodontal disease, and other oral health issues. Conversely, a diet high in sugars, fats, and processed foods was linked to an increased risk of dental problems. Overall, the review emphasized the importance of a balanced and nutritious diet in promoting optimal oral health and preventing oral diseases. The findings underscored the need for public health initiatives and interventions that focus on promoting healthy eating habits and nutritional choices to improve oral health outcomes. Further investigation is warranted to explore the particular mechanisms underlying the link between diet, nutrition, and oral health and to inform evidence-based dietary recommendations for oral health promotion.